Hippocampal GluA1 expression in Gria1−/− mice only partially restores spatial memory performance deficits - Freudenberg, Florian; Resnik, Evgeny; Kolleker, Alexander; Celikel, Tansu; Sprengel, Rolf; Seeburg, Peter H. (Neurobiology of learning and memory, 2016)
Spatial working memory (SWM) is an essential cognitive function important for survival in a competitive environment. In rodents SWM requires an intact hippocampus and SWM expression is impaired in mice lacking the α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid (AMPA) receptor subunit GluA1 (Gria1−/− mice). Here we used viral gene transfer to show that re-expression of GluA1 in the hippocampus can affect the behavioral performance of GluA1 deficient mice. We found that Gria1−/− mice with hippocampus-specific rescue of GluA1 expression (Gria1Hpc mice) are more anxious, less hyperactive and only partly impaired in SWM expression in the Y-maze spatial novelty preference paradigm compared to Gria1−/− mice. However, Gria1Hpc mice still express SWM performance deficits when tested in the rewarded alternation T-maze task. Thus, the restoration of hippocampal function affects several behaviors of GluA1 deficient mice - including SWM expression - in different tasks. The virus-mediated GluA1 expression in Gria1−/− mice is not sufficient for a comprehensive SWM restoration, suggesting that both hippocampal as well as extra-hippocampal GluA1-containing AMPA receptors contribute to SWM.
Im Titel sind ''-'' und "/" hochgestellt
Gesehen am 03.06.2020